EVALUASI KINERJA SARANA DAN PRASARANA PASAR TRADISIONAL : (STUDI KASUS PASAR ANYAR KOTA BANDUNG) - Irawati; Tri Setyowati; Rima Midiyanti (Jurnal Teknik Sipil, 2022)
Pasar Anyar is an A class people’s market managed by PD. Pasar Bermartabat Bandung. The land of this market has an area of 10,190 m2 and the building has an area of 9,350 m2. In 2017, the trading area for meat and vegetables was constructed, in 2019 the roof was repaired, and in 2021 the management office was repaired. The building of Pasar Anyar has exceeded its economic age and has unorganized trading zones. The facilities and infrastructures are dirty and damaged, also some infrastructure has not available yet. The purpose of this research is to find out the performance of Pasar Anyar’s facilities and infrastructure. This evaluation of Pasar Anyar uses performance indicators of facilities and infrastructure, namely accessibility, facilities, convenient, and spacial and building layout. The research methods used are descriptive with qualitative and quantitative approaches, data analysis techniques with building and technical statistical requirements, and data collection techniques using observations, interviews, questionnaires, and documentation studies. The results showed that the facilities and infrastructure of Pasar Anyar are not in accordance with people’s market standards. Therefore, redeveloping the damaged facilities and infrastructures is needed to be done. Additionally, build infrastructures that has yet to be available is required.